Bupropion Binds to Two Sites in the Torpedo Nicotinic Acetylcholine Receptor Transmembrane Domain: A Photoaffinity Labeling Study with the Bupropion Analog [(125)I]-SADU-3-72 - Pandhare, Akash (2012)
Bupropion, a clinically-used antidepressant and smoking-cessation drug, acts as a noncompetitive antagonist of nicotinic acetylcholine receptors (nAChRs). To identify its binding site(s) in nAChRs, we developed a photoreactive bupropion analog, (±)-2-(N-tert-butylamino)-3′-[(125)I]-iodo-4′-azidopropiophenone (SADU-3-72). Based upon inhibition of [(125)I]SADU-3-72 binding, SADU-3-72 binds with high affinity ((IC)50 = 0.8 μM) to the Torpedo nAChR in the resting (closed channel) state and in the agonist-induced desensitized state, and bupropion binds to that site with three-fold higher affinity in the desensitized (IC(50) = 1.2 μM) than in the resting state. Photolabeling of Torpedo nAChRs with [(125)I]SADU-3-72 followed by limited in-gel digestion of nAChR subunits with endoproteinase Glu-C established the presence of [(125)I]SADU-3-72 photoincorporation within nAChR subunit fragments containing M1-M2-M3 helices (αV8-20K, βV8-22/23K and γV8-24K) or M1-M2 helices (δV8-14). Photolabeling within βV8-22/23K, γV8-24K and δV8-14 was reduced in the desensitized state and inhibited by ion channel blockers selective for the resting (tetracaine) or desensitized (thienycyclohexylpiperidine (TCP)) state, and this pharmacologically specific photolabeling was localized to the M2-9 leucine ring (δLeu265, βLeu257) within the ion channel. In contrast, photolabeling within the αV8-20K was enhanced in the desensitized state and not inhibited by TCP, but was inhibited by bupropion. This agonist-enhanced photolabeling was localized to αTyr(213) in αM1. These results establish the presence of two distinct bupropion binding sites within the Torpedo nAChR transmembrane domain: a high affinity site at the middle (M2-9) of the ion channel and a second site near the extracellular end of αM1 within a previously described halothane (general anesthetic) binding pocket.